2000
DOI: 10.1073/pnas.97.15.8439
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of CD26 by mannose 6-phosphate/insulin-like growth factor II receptor contributes to T cell activation

Abstract: CD26 is a T cell activation antigen known to bind adenosine deaminase and have dipeptidyl peptidase IV activity. Cross-linking of CD26 and CD3 with immobilized mAbs can deliver a costimulatory signal that contributes to T cell activation. Our earlier studies revealed that cross-linking of CD26 induces its internalization, the phosphorylation of a number of proteins involved in the signaling pathway, and subsequent T cell proliferation. Although these findings suggest the importance of internalization in the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
93
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 44 publications
1
93
1
Order By: Relevance
“…9A) and by resting monocytes (20). Although it has been reported that the 300-kDa protein M6P͞IGF-IIR was linked with CD26 on the T cell surface to enhance CD26-mediated costimulation (8), no protein with a molecular mass of Ϸ300 kDa was detected by our purification method. An explanation may be that M6P͞IGF-IIR might compete with ADA to bind CD26 because we used CD26-ADA Sepharose bead columns to purify potential CD26-associated molecules.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…9A) and by resting monocytes (20). Although it has been reported that the 300-kDa protein M6P͞IGF-IIR was linked with CD26 on the T cell surface to enhance CD26-mediated costimulation (8), no protein with a molecular mass of Ϸ300 kDa was detected by our purification method. An explanation may be that M6P͞IGF-IIR might compete with ADA to bind CD26 because we used CD26-ADA Sepharose bead columns to purify potential CD26-associated molecules.…”
Section: Discussionmentioning
confidence: 77%
“…Importantly, DPPIV enzyme activity is required for CD26-mediated T cell costimulation (7). More recently, we have shown that internalization of CD26 after crosslinking is mediated in part by the mannose-6-phosphate͞ insulin-like growth factor II receptor (M6P͞IGF-IIR), and that CD26-M6P͞IGFIIR interaction plays a role in CD26-induced T cell costimulation (8).…”
mentioning
confidence: 99%
“…Furthermore, since hDPP4 is known as a multifunctional peptidase that not only functions with hydrolase but also is involved in T-cell activation, lymphocyte-epithelial cell adhesion, and the pericellular proteolysis of the extracellular matrix (49)(50)(51)(52), bacterial DPP4 might have additional roles in periodontopathic patients. In conclusion, we propose a novel molecular mechanism of periodontitis-diabetes interaction, in which periodontopathic bacterial DPP4 adversely impacts glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…First, binding to the M6P/IGF2R could be required for proper localization of CREG. The receptor could concentrate CREG at the cell surface and promote an efficient interaction of CREG with another cell surface protein, as shown for uPAR (Nykjaer et al, 1998), or mediate internalization of CREG to localize it to its site of action, as shown for CD26 (Ikushima et al, 2000). The immunofluorescence data presented here In the second model, the binding of CREG to M6P/ IGF2R could alter receptor trafficking as shown for RA (Kang et al, 1998), and/or the binding to other ligands as shown for beta-galactosidase (MacDonald et al, 1988;Waheed et al, 1988;Kiess et al, 1990).…”
Section: Discussionmentioning
confidence: 99%